La Basilica di San Miniato al Monte di Firenze (1018-2018) Storia e documentazione - Gianni, Francesco; Salvestrini, Francesco (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2021)
Between the 11th and the 20th century, the monastery of San Miniato al Monte in Florence played a leading role in the religious and cultural life of the city. The volume analyses for the first time the historical and documentary evolution of this regular institute, famous almost only from the architectural and artistic points of view. The book focuses the period of the bishop's patronage in the 11th century, when the monastery and some of its members emerged in the context of the ecclesiastical reform, and continues with the study of the the Olivetan monks community, during the 14th-16th centuries, to arrive at the important structural and functional, but also semantic, transformations of the monument between the 18th century and the contemporary times.